Lethal standoff [large type] - Mills, DiAnn (Center Point Large Print, 2024)
"Hostage negotiator Carrington Reed is called to the scene when reports come in that fifteen hostages are being held by the Kendrix brothers in an abandoned house in south Texas. When she arrives on site, Carrington quickly learns that the brothers are armed and refuse to release their victims, a group of undocumented immigrants, until the local police identify their father's murderer. Working closely with Levi Ehrlich, a handsome investigative reporter who has covered some of Carrington's negotiations in the past, she finds herself being undeniably drawn to him. Carrington digs deeper into the death of the Kendrixes' father and begins to notice that some details surrounding his death aren't adding up. As Carrington investigates the brothers' claims and tries to piece together their motive for taking innocent people captive, it soon becomes clear that revenge for their father's death may not be what they're really bargaining for after all. To protect the hostages, Carrington must get to the bottom of one family's secret and the truth they're trying so hard to hide before time runs out."--